Insights into periodontitis: pathogenesis, host response, and antibiotic strategies - Aryani Hayuningtyas, Ria; Endriyana, Jessica; Natassya, Priska (Jurnal Kedokteran Gigi Terpadu, 2024)
This paper provides a comprehensive exploration of periodontitis, a persistent and multifaceted inflammatory condition impacting tooth-supporting structures. The authors investigate the intricate relationship between causative factors, local microbiota, and the host immune response. The disarrayed regulation of cytokines, specifically IL-1, IL-6, and TNF, is highlighted for its pivotal role in triggering or hastening periodontitis onset. The study delves into the host response, emphasizing the delicate equilibrium needed between the immune system and microbiota. The categorization of periodontal pathogenic bacteria, with a focus on the highly pathogenic Phorphyromonas gingivalis and its virulence factors, is explored. Antibiotic efficacy in the context of rising resistance is discussed, encompassing commonly used antibiotics and proposing alternative strategies like plant extracts and bacteriocins. The study advocates for comprehensive therapeutic approaches that integrate antibiotics with alternative methods to effectively address the complex nature of periodontal diseases